MASS-TRANSFER OF HELIUM, NEON, ARGON, AND XENON THROUGH A STEADY-STATE UPPER-MANTLE - Porcelli, D; Wasserburg, G (1995)
We have examined the steady-state upper mantle model for helium, neon, argon, and xenon following the mass transfer approach presented by Kellogg and Wasserburg (1990) for helium and Porcelli and Wasserburg (1995a) for xenon. The model explains the available observational data of mantle helium, neon, argon, and xenon isotope compositions and provides specific predictions regarding the rare gas isotopic compositions of the lower mantle, subduction of rare gases, and mantle rare gas concentrations. Rare gases in the upper mantle are derived from mixing of rare gases from the lower mantle, subducted rare gases, and radiogenic nuclides produced in situ. Isotopic shifts in the closed system lower mantle are due to decay of uranium and thorium decay series nuclides, 40K, 129I, and 244Pu over 4.5 Ga, while isotopic shifts in the steady-state upper mantle are due to decay of uranium and thorium series nuclides, and 40K over a timescale of ∼1.4 Ga. The model predicts that the shift in 21Ne/22Ne in the upper mantle relative to that in the lower mantle is the same as that for 4He/3He between the mantle reservoirs. This is compatible with the available data for MORB and ocean islands. Subduction of atmospheric helium and neon is not significant. All of the 40Ar in the lower mantle has been produced by 40K decay in the lower mantle. In the upper mantle, 40K decay further increases the radiogenic 40Ar from the lower mantle by a factor of ∼3. The calculated minimum lower mantle 40Ar 36Ar ratio is substantially greater than the atmospheric ratio. The inferred rare gas relative abundances of the lower mantle are different from those of the atmosphere and are consistent with possible early solar system reservoirs. Both the calculated 3He 22Ne and 20Ne 36Ar ratios of the lower mantle are within the range for meteorites with 'solar' neon isotope compositions. The 130Xe 36Ar ratio of the lower mantle is greater than that of the atmosphere, and may be possibly as high as the ratio found for meteoritic "planetary" rare gases. The model treats the atmosphere as a separate reservoir with rare gas isotope compositions that are distinct from those in the mantle. If the Earth originally had uniform concentrations of rare gases as represented by those in the lower mantle, then degassing of the upper mantle would have provided only a small proportion of the nonradiogenic rare gases presently in the atmosphere. The remainder may have been derived from late-accreted material with a much higher concentration of rare gases than the lower mantle. However, the amount of radiogenic 129Xe and 136Xe in the atmosphere as well as the lower mantle implies a substantial loss of rare gases. It is most likely that rare gases have been lost during late accretion and/or during; the hypothesized moon-forming impact. The nonradiogenic rare gases in the atmosphere were then supplied by subsequently accreted material with nonradiogenic xenon, possibly in comets. Fractionation of atmospheric xenon isotopes relative to other early solar system components must have occurred either on the late-accreting materials or during subsequent loss from the Earth. © 1995.